2004
DOI: 10.1023/b:cbto.0000029466.08607.86
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione depletion modulates methanol, formaldehyde and formate toxicity in cultured rat conceptuses

Abstract: The proposed use of methanol (H3COH) as an alternative to fossil fuels has prompted concern about potential health risks resulting from widespread environmental exposure. Methanol is teratogenic in rodents and, although the exact toxic species is not known, teratogenesis may result from the enzymatic biotransformation of H3COH to formaldehyde (CH2O) and formic acid causing increased biological reactivity and toxicity. A protective role for the antioxidant glutathione (GSH) has been described for H3COH, CH2O an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…However, in animals coexposed to methanol and ethanol, the levels were comparable to those in the controls. The decrease in glutathione levels is in accordance with previous studies showing increased free radical generation during methanol toxicity is associated with decreased cellular GSH levels [28,29]. The restoration of GSH levels toward the normal in the methanol and ethanol cotreated animals might be due to the preference of ethanol metabolism over methanol resulting in slower rate of formaldehyde formation.…”
Section: Discussionsupporting
confidence: 91%
“…However, in animals coexposed to methanol and ethanol, the levels were comparable to those in the controls. The decrease in glutathione levels is in accordance with previous studies showing increased free radical generation during methanol toxicity is associated with decreased cellular GSH levels [28,29]. The restoration of GSH levels toward the normal in the methanol and ethanol cotreated animals might be due to the preference of ethanol metabolism over methanol resulting in slower rate of formaldehyde formation.…”
Section: Discussionsupporting
confidence: 91%
“…Animals were kept on a 12 h-12 h light/dark cycle, and were given food and water ad libitum . On the day of each experiment dams were anesthetized, exsanguinated, and sacrificed as previously described [19]. Conceptuses were explanted on GD10, prepared for culture, and placed into 60 ml culture bottles containing 10 ml of control media.…”
Section: Methodsmentioning
confidence: 99%
“…To optimize growth, bottles were gassed on GD10 after explantation with 20% O 2 /5% CO 2 and on the morning of GD11 with 95% O 2 /5% CO 2 . Culture bottles were incubated at 37°C in a roller apparatus throughout the culture period as described previously [10, 19, 20]. …”
Section: Methodsmentioning
confidence: 99%
“…Harris et al . exposed mouse whole-embryos (gestation day 10–12) to formaldehyde in culture medium and found that formaldehyde had deleterious effects on embryo growth and viability and produced a depletion of glutathione (GSH) in the visceral yolk sac and embryo [90]. Neuropore closure, crown-rump length and somite number were reduced by formaldehyde.…”
Section: Experimental Animal Studiesmentioning
confidence: 99%